Study on Sediment Regime Changes in Downstream of the Ba River, Vietnam under the Impact of Reservoirs System - Giang, Nguyen Tien; Thao, Hoang Thu; Vinh, Tran Ngoc; Binh, Pham Duy Huy; Quan, Vu Duc (VNU Journal of Science: Earth and Environmental Sciences; Vol 33 No 4, 2017)
Reservoirs system in the upstream of Ba River has been affecting to the hydrology and sediment regime in the downstream. Sediment imbalance causes consequences such as erosion at river bank, lack of sediment supply to downstream areas and deposition/erosion in estuaries. This study focused on a quantitative assessment of the impact of Ba Ha reservoir and Hinh river reservoir on sediment regime at the Cung Son hydrological station (12 km downstream of Ba Ha reservoir and 45 km from the mouth of the Da Dien river). Research used analytical and statistical methods with flow and suspended sediment data measured at the Cung Son hydrological station from 1977 to 2016. The results show that the system of these two reservoirs has a huge impact to the sedimentation regime, especially after the operation of Ba Ha reservoir. The average amount of sediment in the period before and after 2008 significantly reduced from about 2.5 million to about 1 million tons per year. Keywords Reservoir, Ba River, Sediment regime, suspened sediment, Cung Son station References 1. T. K. S. Abam, Impact of dams on the hydrology of the Niger Delta, Bulletin of Engineering Geology and the Environment, 57(3), (1999), 239. 2. José D. Carriquiry, Alberto Sánchez, Victor F. Camacho-Ibar, Sedimentation in the northern Gulf of California after cessation of the Colorado River discharge, Sedimentary Geology, 144, (2001) 37. 3. M. B. de Paula, C. Gomes Ade, D. Natal, A. M. Duarte, L. F. Mucci, Effects of Artificial Flooding for Hydroelectric Development on the Population of Mansonia humeralis (Diptera: Culicidae) in the Parana River, Sao Paulo, Brazil, J Trop Med, (2012), 598. 4. Wayne D. Erskine, Downstream geomorphic impacts of large dams: the case of Glenbawn Dam, NSW, Applied Geography, 5(3), (1985), 195. 5. Alfy Morcos Fano, The Impact of Human Activities on the Erosion and Accretion of the Nile Delta Coast, Journal of Coastal Research, 11(3), (1995), 821. 6. Nguyễn Tiền Giang, Đề tài "Nghiên cứu cơ sở khoa học để xác định cơ chế bồi lấp, sạt lở và đề xuất các giải pháp ổn định các cửa sông Đà Diễn và Đà Nông tỉnh Phú Yên phục vụ phát triển bền vững cơ sở hạ tầng và kinh tế xã hội" (2015-2018) 7. Nguyễn Tiền Giang, Nguyễn Thị Hương, Nguyễn Việt, Trần Thiết Hùng, Nguyễn Ngọc Hà, Trần Ngọc Anh, Trần Ngọc Vĩnh, Đánh giá sự biến đổi chế độ thủy văn hạ lưu lưu vực sông Ba dưới tác động của hệ thống hồ chứa, Tạp chí Khoa học ĐHQGHN: Các Khoa học Trái đất và Môi trường, 21, (2016), 12. 8. Nguyễn Xuân Lâm, Nguyen Quang An, Nghiên cứu đánh giá tác động điều tiết hồ chứa đến chế độ dòng chảy kiết hạ du lưu vực sông Mã, Tạp chí Khoa học Kỹ thuật Thủy lợi và Môi trường , 44, (2014), 88. 8. R. T. Kingsford, Ecological impacts of dams, water diversions and river management on floodplain wetlands in Australia, Austral Ecology, 25(2), (2000), 109. 9. John D. Milliman, Robert H. Meade, World-Wide Delivery of River Sediment to the Oceans, The Journal of Geology, 91(1), (1983) 10. Geoffrey E. Petts, Complex response of river channel morphology subsequent to reservoir construction, Progress in Physical Geography, 3(3), (1979), 329 11. Daniel Jean Stanley, Andrew G. Warne, Nile Delta in Its Destruction Phase, Journal of Coastal Research, 14, (1998), 794 12. A. S. Trenhaile, Coastal Dynamics and Landforms, Oxford, U. K (1997).